2019
DOI: 10.1016/j.molcel.2019.07.021
|View full text |Cite
|
Sign up to set email alerts
|

mTORC1 Activation Requires DRAM-1 by Facilitating Lysosomal Amino Acid Efflux

Abstract: SummarySensing nutrient availability is essential for appropriate cellular growth, and mTORC1 is a major regulator of this process. Mechanisms causing mTORC1 activation are, however, complex and diverse. We report here an additional important step in the activation of mTORC1, which regulates the efflux of amino acids from lysosomes into the cytoplasm. This process requires DRAM-1, which binds the membrane carrier protein SCAMP3 and the amino acid transporters SLC1A5 and LAT1, directing them to lysosomes and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 50 publications
3
47
0
Order By: Relevance
“…Indeed, in RTH-149 cells, the mTOR appeared to be strongly activated by EAA when the cells were preloaded with glutamine. This observation would indicate that RTH-149 cells sense amino acids and activate the mTOR following mechanisms shared between trout, mice and human cell lines [ 39 , 40 ] Altogether, experiments conducted so far in RTH-149 cells tend to demonstrate that molecular mechanisms leading to GCN2, autophagy and mTOR activation have been conserved throughout evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in RTH-149 cells, the mTOR appeared to be strongly activated by EAA when the cells were preloaded with glutamine. This observation would indicate that RTH-149 cells sense amino acids and activate the mTOR following mechanisms shared between trout, mice and human cell lines [ 39 , 40 ] Altogether, experiments conducted so far in RTH-149 cells tend to demonstrate that molecular mechanisms leading to GCN2, autophagy and mTOR activation have been conserved throughout evolution.…”
Section: Discussionmentioning
confidence: 99%
“…BioID2 was fused to the C-terminus of DRAM1 without breaking the signal peptide in the N-terminus. The reported DRAM1-interacted proteins such as SLC1A5, SLC7A5 and SLC3A2 7 are also included in the list. Intriguingly, we found that DRAM1 interacted with EPS15 (epidermal growth factor receptor pathway substrate 15), a substrate for the tyrosine kinase of EGFR.…”
Section: Discussionmentioning
confidence: 99%
“…DNA damage-regulated autophagy modulator 1 (DRAM1) encodes a six transmembrane protein mainly located in lysosomes to induce autophagy and is downregulated in multiple human cancers 6 . DRAM1 directs newly synthesized amino acid transporters to lysosomes and drives lysosomal amino acid efflux 7 . In addition to lysosomes, DRAM1 isoforms are also partly localized to peroxisomes, autophagosomes, and the endoplasmic reticulum 8 .…”
Section: Introductionmentioning
confidence: 99%
“…DRAM1 was shown to interact with the pro-apoptotic protein BAX, which recruited BAX to lysosomes and initiated cell death via release of lysosomal cathepsin B (Guan et al, 2015). Recently, it has also been found that DRAM1 is required for efficient activation of mTORC1, a nutrient-sensing complex that functions at the lysosome (Beaumatin et al, 2019). DRAM1 facilitates activation of mTORC1 by binding the membrane carrier protein SCAMP3 and the amino acid transporters SLC1A5 and LAT1, thereby directing them to lysosomes (Beaumatin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has also been found that DRAM1 is required for efficient activation of mTORC1, a nutrient-sensing complex that functions at the lysosome (Beaumatin et al, 2019). DRAM1 facilitates activation of mTORC1 by binding the membrane carrier protein SCAMP3 and the amino acid transporters SLC1A5 and LAT1, thereby directing them to lysosomes (Beaumatin et al, 2019). An emerging theme is that DRAM1 functions at the interface between lysosomes, signalling complexes, and other vesicles by binding and directing effector molecules.…”
Section: Discussionmentioning
confidence: 99%